A Pilot Study to Evaluate the Role of Obesity and Genetic Variants in Serum C-Reactive Protein Response to an Acute Fructose Load - Sai Sravani Vennam; Valentina Talevi; Geethika Venkataraman; Rayyan Ahmed Syed; Xinruo Zhang; Baba B. Mass; Venkata Saroja Voruganti (Lifestyle Genomics)
Introduction: Excess fructose intake has been linked to increased risk of dyslipidemia, insulin resistance, hyperuricemia, inflammation, and obesity. In this human study, we investigated if serum C-reactive protein (CRP) concentrations change after fructose consumption, and whether genetic variants and obesity status influence this change. Methods: Blood was drawn before and at four time points after administration of a fructose load (n = 57). Serum concentrations of CRP were measured, and 11 single nucleotides polymorphisms (SNPs) (rs1205, rs1417938, rs1470515, rs3093068, rs6588158, rs16842568, rs2259820, rs157581, rs2794521, rs3093062, rs17700633), previously associated with serum CRP were genotyped and assessed for their association with CRP levels. Results: Participants identifying as White (n = 37) had higher mean CRP levels across all time points compared to those identifying as Black (n = 20). Participants with obesity (body mass index ≥30 kg/m2) (n = 25) were younger and had higher mean CRP levels throughout the study period compared to those without (n = 32). All SNPs were in Hardy-Weinberg equilibrium and their effect allele frequencies ranged between 11 and 96%. Baseline CRP was associated with CRP SNPs rs1417938 and rs2794521 (p < 0.005); rs2794521 was also associated with CRP response to fructose challenge (p < 0.005). The variability in response to fructose and genetic associations was mainly observed in individuals without obesity. Obesity status was associated with early changes in CRP (0–30 min and 30–60 min) whereas CRP SNPs were associated with later changes (60–120 min and 120–180 min). Conclusion: Changes in serum CRP were associated with obesity status or SNPs based on the time elapsed since fructose ingestion. Larger studies are needed to confirm and validate these associations.